Functional Properties of Modern Supplemental Feeding Products - Tatiana V. Turti; Leyla S. Namazova-Baranova; Irina A. Belyaeva; Elena A. Bakovich (Педиатрическая фармакология, 2020)
The first thousand days of the child’s life are the critical window for formation of his health. Rationality, balance, availability of nutrition, creation of conditions for development of tolerance to food have the highest importance in this period. Healthy food and use of functional products can prevent the development of certain chronic non-communicable diseases such as cardiovascular diseases, metabolic syndrome, obesity, type 2 diabetes, allergies according to recent international studies. The unstable balance between formation of tolerance and effector immune reactions can be disrupted due to improper feeding during the implementation of supplemental feeding. Thus, functional gastrointestinal disorders can transform into pathological conditions. It is relevant to determine the range of supplemental feeding products that have functional properties, and so to use them during this window of tolerance in the diet of the child who has risk of development of allergies with functional gastrointestinal disorders.